Career Calling as the Mediator and Moderator of Job Demands and Job Resources for Job Satisfaction in Health Workers: A Cross-Sectional Study - Huang, Xianhong; Chen, Hanlin; Gao, Yuan; Wu, Jin; Ni, Ziling; Wang, Xiaohe; Sun, Tao (Frontiers in Psychology, 2022)
Job satisfaction of health professionals is a key determinant of the quality of health services and even affects the development of the healthcare system. In this study, we sought to explore the mechanism by which job demands, job resources, and career calling affect the job satisfaction of health professionals. Our findings may provide insights for increasing their job satisfaction and improving the quality of health services. We conducted a questionnaire survey of 1117 health workers in Hangzhou; t-test, Chi-squared analysis, hierarchical linear regression was used to analyze the state of job satisfaction of health personnel and the associated factors; path analysis with the Structural Equation Model was used to explore and verify the effects of job resources, demands, and career calling on job satisfaction, as well as their mechanism. Social support, performance feedback, working conditions, and career calling had significant positive effects on job satisfaction of health professionals, whereas work-family conflict and emotional requirements for work had significant negative effects. Path analysis indicated that job resources, demands, and career calling directly affected job satisfaction; job resources and demands showed indirect effects on job satisfaction with career calling as a mediator. Career calling had a positive moderating effect in the path of "job resources–job satisfaction", and a negative moderating effect in the path of "job demands–job satisfaction". In Conclusion, hospital administrators should provide more job resources for health workers and formulate reasonable job demands while paying close attention to work-related pressure. Hospital administrators and health departments need to improve hospital policies and inculcate a sense of belonging and career calling among health professionals. Education and evaluation of career calling need to be accorded more attention so that healthcare workers can perceive a stronger sense of calling and achievement, and hence a higher degree of job satisfaction.